Transformasi Orientasi Pemustaka Pada Tahun Politik Pemilu 2024 - Agung Nugrohoadhi (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The need for information for human beings has its own characteristics and differences so that each has an unequal portion in needing the necessary information. They need information because it is considered to be able to add insight so that they can move their minds and behavior to find answers to their ignorance. The development of information through various existing sources causes an abundance of information that is not necessarily all that is needed. The need for this information depends on the background and limited information available at the time. Other implications of the advancement of digital technology will have various impacts. Starting from cultural changes that have shifted the cultural fabric of society that has lived in the midst of Indonesian society for a long time, to information technology that makes information sources very accessible to the public with content diverse content, both from a positive side that can build human civilization or it will plunge humanity into a moral decline that was previously upheld. Shifting moral values ​​into something that must be